2001
DOI: 10.1016/s0167-4889(00)00121-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional testing of putative oligopeptide permease (Opp) proteins of Borrelia burgdorferi: a complementation model in opp− Escherichia coli

Abstract: Studies of the protein function of Borrelia burgdorferi have been limited by a lack of tools for manipulating borrelial DNA. We devised a system to study the function of a B. burgdorferi oligopeptide permease (Opp) orthologue by complementation with Escherichia coli Opp proteins. The Opp system of E. coli has been extensively studied and has well defined substrate specificities. The system is of interest in B. burgdorferi because analysis of its genome has revealed little identifiable machinery for synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…While the B. burgdorferi opp operon is chromosomally encoded, at least two other OppA orthologues have been identified on borrelial plasmids (oppA-IV on cp26 and oppA-V on lp-54). In previous studies using a complementation system with the E. coli integral membrane proteins OppB and OppC, the ability of the borrelial OppA orthologues to bind and facilitate transport of peptides was confirmed (10).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…While the B. burgdorferi opp operon is chromosomally encoded, at least two other OppA orthologues have been identified on borrelial plasmids (oppA-IV on cp26 and oppA-V on lp-54). In previous studies using a complementation system with the E. coli integral membrane proteins OppB and OppC, the ability of the borrelial OppA orthologues to bind and facilitate transport of peptides was confirmed (10).…”
mentioning
confidence: 87%
“…Whereas E. coli DppA appears to have fairly narrow substrate specificity, OppA in other bacteria has been shown to have very broad substrate specificity (6, 14-16, 20, 21). In comparison to E. coli OppA, the B. burgdorferi OppA proteins appear to have overlapping but narrower specificities, allowing for the potential of separate roles for each OppA protein (10). We were interested in the mechanisms of regulation and expression of the B. burgdorferi OppA proteins and whether they could be differentially expressed under changing environmental conditions.…”
mentioning
confidence: 99%
“…Western blotting was performed as described previously (18) to confirm the identities of the purified proteins. Antibodies to the OppA proteins were kind gifts from James Bono and Patricia Rosa (Rocky Mountain Laboratories, Hamilton, Mont.…”
Section: Iefmentioning
confidence: 99%
“…Two other OppA orthologues (OppA-4 and OppA-5) have been identified from borrelial plasmids (cp26 and lp-54, respectively). Lin et al confirmed the ability of the B. burgdorferi OppA orthologues to transport tripeptides by using a complementation system in E. coli (18).…”
mentioning
confidence: 95%
“…A number of bacterial species cannot synthesize amino acids, fatty acids, and certain other essential elements (Matthews, 1975;Lin et al, 2001), and uptake essential nutrients from their environment. The ABC transporters mediate a large fraction of the nutrient uptake capacity in bacteria.…”
Section: Introductionmentioning
confidence: 99%